2022
DOI: 10.1021/acs.jmedchem.2c00944
|View full text |Cite
|
Sign up to set email alerts
|

N-Benzyl Benzamide Derivatives as Selective Sub-Nanomolar Butyrylcholinesterase Inhibitors for Possible Treatment in Advanced Alzheimer’s Disease

Abstract: Herein, we report a series of selective sub-nanomolar inhibitors against butyrylcholinesterase (BChE). These compounds, bearing a novel N-benzyl benzamide scaffold, inhibited BChE with IC 50 from picomolar to nanomolar. The inhibitory activity was confirmed by the surface plasmon resonance assay, showing a sub-nanomolar K D value, which revealed that the compounds exert the inhibitory effect through directly binding to BChE. Several compounds showed neuroprotective effects verified by the oxidative damage mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
(72 reference statements)
2
18
0
Order By: Relevance
“…Different to AChE, levels of butyrylcholinesterase (BChE) seem to increase during disease progression, marking it as a promising target for mid- and late-stage treatment of AD . Several studies by us and others could already underline beneficial effects of BChE inhibition in vivo regarding neuroprotective properties. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Different to AChE, levels of butyrylcholinesterase (BChE) seem to increase during disease progression, marking it as a promising target for mid- and late-stage treatment of AD . Several studies by us and others could already underline beneficial effects of BChE inhibition in vivo regarding neuroprotective properties. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…In the past 5 years, a number of potent and selective BChE inhibitors have been developed through virtual screening and a series of structural optimizations (Figure ), such as S11-1014 ( 4 ), S08-3009 ( 5 ), and S06-1011 ( 6 ). Among all these compounds, S11-1014 shows highly potent and selective inhibitory activity against BChE ( eq BChE IC 50 = 0.15 ± 0.06 nM, h BChE IC 50 = 0.08 ± 0.03 nM, h BChE K D = 3.18 nM, eq BChE, and h BChE are butyrylcholinesterase from equine and human serum, respectively). At the same time, this compound possesses reasonable physicochemical properties and relatively suitable BBB permeability.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, we found that selective BChE inhibitors can protect against neuronal damage . Therefore, we next assessed the cytoprotective effect of the compounds against glutamate- and hydrogen peroxide-induced cell damage using the MTT assay (glutamate and hydrogen peroxide were carried out on SH-SY5Y and PC12 cells, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations